A SELECTION OF ISSUES CONCERNING FRIDAY AS THE DAY OF PENANCE IN THE ASPECT OF CANON LAW - Czaja, Arkadiusz Mirosław (Review of European and Comparative Law, 2020)
As for the days of penance the Church legislator set the minimum which Catholics should obey as common practice . Therefore, the mandatory days of penance have been established in the Roman Catholic Church . Among these, there are all Fridays of the entire litrugical year . The purpose of this study is to present one particular type of sacred time from the perspective of law as well as to take part in the discussion on the sanctifying influence of Friday on Catholics . Friday is of special significance for spirituality of all the faithful, as it is closely related to which concern the penance on Friday, both with other people, in pub-lic, as well as individually, in private, is a symbol of cooperation with the universal Church, hence Catholics ought to take acts of mortification and devote them-selves to prayer frequently .